Alcohol use and consequences in matriculating US college students by prescription stimulant/opioid nonmedical misuse status. (November 2019) - Schepis, Ty S.; Acheson, Shawn; Zapp, Daniel; Swartzwelder, H. Scott
Abstract: Background: US college students have elevated prescription opioid and stimulant misuse rates, with frequent alcohol use and alcohol-related consequences (ARCs). To date, though, no research has examined relationships between opioid and/or stimulant misuse and alcohol quantity/frequency or ARC variables in college students. Methods: The 2016–17 AlcoholEDU for College ™, a web-based alcohol prevention program, provided data ( n = 491, 849). Participants were grouped into past 14-day: (1) no misuse; (2) opioid misuse only; (3) stimulant misuse only; and (4) combined misuse. Using multilevel logistic regressions, groups were compared on 14-day alcohol use odds, and among those with use, odds of any ARCs and specific ARCs (e.g., hangover). Multilevel negative binomial regressions compared group members with alcohol use on 14-day total drinks, maximum 24-h drinks and drinking days. Results: Alcohol use and any ARCs odds were highest in the stimulant (odds ratios [OR] = 3.47 and 2.97, respectively) or opioid misuse only groups (ORs = 3.31 and 2.43, respectively), with the combined misuse group intermediate (ORs = 1.63 and 1.29; reference: no misuse). Mean 14-day drinks decreased from those with combined misuse, to those with stimulant misuse only, opioid misuse only and no misuse (8.22, 7.1, 6.67, and 4.71, respectively). Conclusions: College students engaged in 14-day stimulant and/or opioid misuse had higher odds of 14-day alcohol use, higher levels of alcohol use, and a greater likelihood of ARCs, versus students without misuse. These findings suggest that college students with any prescription misuse need alcohol screening, although those with poly-prescription misuse may not need more intensive alcohol interventions. Highlights: We examined college student alcohol use outcomes by prescription misuse status. Opioid and/or stimulant misuse conferred higher alcohol use odds, versus no misuse. Any misuse also conferred higher alcohol-related consequence odds. Combined misuse was not associated with worse outcomes over single class misuse. College student opioid and/or stimulant misuse warrants alcohol use screening.